Atherogenic index of plasma as an additional marker of adverse cardiovascular outcomes - Yu. I. Grinshtein; V. V. Shabalin; R. R. Ruf; S. A. Shalnova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2022)
Aim. Using a representative sample of the Krasnoyarsk Krai population, to evaluate the distribution of the atherogenic index of plasma (AIP), logarithmically transformed ratio of molar concentrations of triglycerides to high-density lipoprotein-cholesterol, and to identify  possible associations between AIP, various cardiovascular diseases, and metabolic parameters.Material and methods. The study included a random representative sample of 1603 residents of the Krasnoyarsk and Berezovsky rural district aged 25-64 years as part of the Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation (ESSE-RF) study. Statistical processing was performed using IBM SPSS v22 and Microsoft Excel 2021 programs. We assessed the prevalence of hypertension (HTN), coronary artery disease, myocardial infarction (MI), stroke and renal dysfunction in the whole sample and in groups with different risk depending on AIP. Differences between groups were tested by Yates’s chi-squared test and were considered significant at p≤0,05.Results. Depending on AIP value, 73,5% of participants were in the low-risk group (AIP <0,10), 10,4% — in moderate risk group (AIP, 0,100,24) and 16,1% — in high-risk group (AIP>0,24). The prevalence of prior MI or stroke in the moderate and high-risk group for AIP was significantly higher than in the low-risk group (p=0,024). A regular increase in HTN prevalence was registered from 42,6% in the lowrisk group to 71,4% in the high-risk group for AIP (p<0,001 for all). There was a significant increase in the proportion of patients with a combination of HTN + elevated low-density lipoprotein cholesterol levels as AIP risk increased — from 28,4% at low risk to 45,2% at high risk. There were no significant differences between AIP risk groups in the prevalence of coronary artery disease and renal dysfunction.Conclusion. AIP is a simple additional estimated parameter that characterizes the atherogenic properties of plasma. Based on a cohort of Krasnoyarsk Krai subjects, an elevated level of AIP is associated with an increased prevalence of MI and strokes. Determination of AIP may be especially useful in the case of normal baseline low-density lipoprotein cholesterol levels.